The evaluation of land suitability toUpland rice (Oryza sativaL.)and Onion (Allium ascalonicum L.) in Kualuh Hulu SubdistrictOfNorth Labuhanbatu District - Khairi Rizki Siregar; zulkifli Nasution; Bintang Sitorus (Jurnal Agroekoteknologi, 2019)
The objective of  this  researchis to evaluate  the  land  suitability Upland rice                (Oryza sativa L.)and Onion (Allium ascalonicumL.) in Kualuh Hulu Subdistrict of North Labuhanbatu  District. The methode of  this  research  is  the  survay method. From the results of the overlay from  the map of soil types, map of topography, and map of height place, retrieved 9  units of land use map. SPL 1 has a land area of22.273,98 hectares, SPL 2 has a land area of 12.248 hectares, SPL 3 has a land area of 8.571,24 hectares, SPL 4 has a land area of 8.015,46hectares, SPL 5 has a land area of 4.736,61 hectares, SPL 6  has a land area of 3.154,86 hectares, SPL 7 has a land area of 2.044,73 hectares, SPL 8 has a land area of 1.445,39 hectares and  SPL 9 has a land area of 946,28hectare. The conclusionof this research showed the highest potential of land suitability classes in set of land 1 is upland rice ( S3 rc ) and onion  ( S3 wa, rc ),in set of land 2 is upland rice (N rc) and onion( N rc ), in set of land 3 is upland rice ( S1 ) and onion ( S3wa ), in set of land4 is upland rice( N rc ) andonion  ( N rc ), in set of land 5 is upland rice (S3 rc ) and onion ( S3 wa rc ), in set of land 6 is upland rice (S1) and onion (S3 wa ), in set of land 7 isupland rice(S3 rc ) and onio (S3 wa rc), in set of land 8 is upland rice (S3 rc ) and onion ( S3 wa rc ) and in set of land 9  is upland rice ( S3 rc ) and onion  (S3 wa rc). Keywords : Land suitability, Onion, Upland rice